Geodesign, urban digital twins and futures - Cureton, Paul; Hartley, Elliot (New York, NY Routledge, 2025)
"This book explores systems, processes and novel technologies for planning, mapping, and designing our built environment. Chapters cover a range of topics such as Urban Digital Twins, GeoBIM, Geodesign and collaborative tools, immersive environments, gamification, and future methods. This book features over 100 international projects and workflows, five detailed case studies, and a companion website. In addition, this book examines Geodesign as an agent for collaboration alongside futuring methods for imagining and understanding our future world"--
Introduction : geodesign, urban digital twins and futures -- Defining the living lab -- Towards urban digital twins --Geodesign and urban digital twins -- Geodesign methods for urban digital twins -- Gaming, worldbuilding and participatory planning -- Conclusion : geodesign, urban digital twins and futures at the edge.
Includes bibliographical references and index.
Keywords: City planning -- Computer simulation; City planning -- Geographic information systems; Digital twins (Computer simulation)